Personality correlates of social attitudes and social distance - Jonáš, Juraj; Doubková, Nikola; Heissler, Radek; Sanders, Edel M; Preiss, Marek (Current issues in personality psychology, 2024)
BACKGROUND: Previous studies have shown that personality traits (i.e., openness to experience, conscientiousness, and agreeableness) relate to prejudicial attitudes. However, one of the aspects of prejudice is social distance; its association with personality traits was overlooked by previous studies. Therefore, this study examines the connection between the Big Five personality traits and social distance toward certain social groups. PARTICIPANTS AND PROCEDURE: Participants from the general population were recruited through leaflets, the institutional webpage, Facebook, and through the project recruitment website and assessed via paper-and-pencil or online form. A total of 214 participants were included (of whom 68.2% were women and the mean age was 32.65, SD = 11.27, range 18-72) who completed the Bogardus Social Distance Scale and the 44-item Big Five Inventory questionnaire. RESULTS: The results showed a relationship between social distance, agreeableness, and openness to experience. Agreeableness seems to lower the social distance toward all studied groups. In comparison, openness to experience seems to lower the social distance towards groups that evoke more polarized attitudes in the majority (e.g., migrants). Furthermore, the influence of demographic characteristics (i.e., age, education level, and gender) is also significant. CONCLUSIONS: This study shows that personality is significantly related to social distancing and expression of prejudicial attitudes. In particular, agreeableness and openness to experience have different effects on social distance and attitudes towards different groups. Further implications are discussed.
Keywords: social distance; BFI-44; Bogardus Social Distance Scale; personality